Strategi Pemasaran Syariah Pada Wirausaha Ternak Bebek - Supriyanto, Supriyanto (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The majority of Indonesians live off livestock. Due to increasing demand, some households in Indonesia have established layer duck farms and broiler duck farms. This is one of the main sectors to fulfill the needs of the Indonesian population. The purpose of this study were (1) to determine the level of welfare for duck farmers in Sumberpakem village, Sumberjambe sub-district, (2) to determine the effect of sharia marketing on increasing consumer demand in Sumberpakem village, Sumberjambe sub-district. This research uses a descriptive qualitative approach to explain sharia marketing strategies in duck entrepreneurship. Observations, interviews, and literature studies were the primary and secondary data sources. Data collection techniques include interviews and observations.The results of this study, the authors obtained the conclusion that sharia marketing strategies in broiler duck entrepreneurs can improve welfare for duck farmers. With sharia marketing can also increase the demand for the number of consumers